Ашигт малтмал олборлох үйл ажиллагаанаас эвдэрсэн газрын үнэлгээ ба нөхөн сэргээх зардал тооцсон дүн (Булган аймгийн Бүрэгхангай сумын жишээн дээр) - Т.Билгүүнтөгс,; Ө.Дэлгэрмаа, (Geological Issues, 2023)
Different landscape types have in Buregkhangai soum, Bulgan aimag. There are stretched out mountains and steppe soils. Mining is serious factors of land degradation especially soil. The development of strip mines, as well as the deposition of overburden spoils and tailings all degrade land resources. Our survey report noticed that since 1992 to 2014 eroded 414.5 hectares land by mining. In this these soil economy evaluation is 10.8 billion tugrik and compensation expense is 10.015 billion tugrik.